Science and religion : an impossible dialogue - Gingras, Yves, 1954- (Cambridge, UK. Polity Press., 2017)
"Today we hear renewed calls for a dialogue between science and religion: why has the old question of the relation between science and religion now returned to the public domain and what is at stake in this debate? To answer these questions, historian and sociologist of science Yves Gingras retraces the long history of the troubled relation between science and religion, from the condemnation of Galileo for heresy in 1633 until his rehabilitation by John Paul II in 1992. He reconstructs the process of the gradual separation of science from theology and religion, showing how God and natural theology became marginalized in the scientific field in the 18th and 19th centuries as the naturalist mode of thinking spread from astronomy and physics to geology, natural history, the origins of the species and the history of societies and religions. Finally, Gingras identifies the forces that have contributed to the recent resurgence of the question of science and religion by analyzing the active role of the Templeton Foundation in promoting the idea of 'dialogue' between science, religion and spirituality. In contrast to the dominant trend among historians of science, Gingras argues that science and religion are social institutions that give rise to incompatible ways of knowing, rooted in different methodologies and forms of knowledge, and that there never was and cannot be a genuine dialogue between them."--Back cover
Introduction -- The theological limits of the autonomy of science -- Copernicus and Galileo : thorns in the sides of popes -- God : from the centre to the periphery of science -- Science censored -- From conflict to dialogue? -- What is a 'dialogue' between science and religion? -- Belief versus science -- Conclusion : betting on reason
Includes bibliographical references (pages 201-235) and index
Keywords: Religion and science -- History